NUMERICAL RESULTS OF DIFFUSION COMBUSTION IN A TURBULENT FLOW OF REACTING GASES - Д.Й.Эргашев (Web of Journals Publishing, 2025)
In this paper, a numerical solution to the problem of the symmetrical flow of methane with respect to the axis under an infinite satellite flux and diffusion combustion is proposed. To simulate the object, dimensional equations in Mises variables of a turbulent boundary layer of interacting gases were used. The equations for the components of the gas mixture are reduced to one equation by introducing the Schwab-Zeldovich function. To solve the problem in the Mises coordinates, a two-layer four-point nonlinear scheme for separating boundaries was used, and the second order was given by the longitudinal coordinate. The iterative process was used due to the nonlinearity of the equations of accumulation and displacement of substations. Individual results of the numerical experiment are presented.
Keywords: Turbulent jet, gas mixture, diffusion flame, velocity, total enthalpy, finite differences, computational experiment.